Peduncular Hallucinosis: A Case Report - Penney, Lauren (the Academic Division of Ochsner Clinic Foundation, 2014)
BACKGROUND: Peduncular hallucinosis is a rare form of visual hallucination often described as vivid, colorful visions of people and animals. The exact pathophysiology is unknown; however, most cases have been described in relation to lesions in the thalamus or midbrain. CASE REPORT: We present the case of a 59-year-old female with peduncular hallucinosis associated with infarction in the right basal ganglia with the background of malignant hypertension. The patient's visual hallucinations decreased without pharmaceutical treatment by the time of discharge and on further follow-up had resolved completely. CONCLUSION: We believe ours is one of few reported cases of peduncular hallucinosis in a patient with an infarct isolated to the basal ganglia (striatum and globus pallidus).